2006
DOI: 10.1088/0957-0233/17/6/020
|View full text |Cite
|
Sign up to set email alerts
|

The interference effect in an optical beam deflection detection system of a dynamic mode AFM

Abstract: Optical beam deflection detection is one of the main techniques used to detect the vibrating amplitude of dynamic mode atomic force microscope cantilevers. Due to the limitations of optical beam deflection detection systems and cantilevers, light leakage of the incident laser beam around the cantilevers can occur. An interference effect between the reflected beam from the cantilever and some scattered light from the specimen surface occurs, and an interference error in the probe tip–specimen approaching curve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…It scatters on the surface of a sample and may interfere with the light scattered from a reflective (back side) part of the cantilever. This phenomenon has been reported for both contact [5] and dynamic (tapping) [6] AFM modes.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…It scatters on the surface of a sample and may interfere with the light scattered from a reflective (back side) part of the cantilever. This phenomenon has been reported for both contact [5] and dynamic (tapping) [6] AFM modes.…”
Section: Introductionsupporting
confidence: 68%
“…Analysis of this effect (see for example [6]) suggests that only hardware related issues result in the interference. For example for a laser diode wavelength (λ =670 nm) according simple equation for the two-beam interference Λ = λ/(1 + cos(α)) , where α = 25 o is the angle between cantilever and the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, optical interference due to laser light spilling over the cantilever and then reflecting from the surface can interfere with laser light reflecting from the back of the cantilever resulting in periodic low frequency oscillations [ 95 ]. It was demonstrated that images taken over smooth or highly reflective surfaces in contact AFM mode can be affected by the optical interference artifacts that may have variable influence on the image contrast and surface roughness parameters derived from the image [ 106 ], while in dynamic mode AFM interference could cause 10 nm (2%) error in height measurements of the structures 500 nm in height [ 107 ]. In some cases optical interference can be reduced or eliminated by moving the cantilever to a different location on the surface, using cantilevers with reflective coating or having an adequate location of the focused laser spot [ 107 ].…”
Section: Resolution Sensitivity and Accuracy For Single Molecule Meamentioning
confidence: 99%
“…An important error source in optical detection based SPMs (i.e., nearly all commercial systems) is the interference of light which misses cantilever and is reflected off the sample surface towards the beam deflection detector [ 122 , 123 ]. It can be modelled using simple geometrical optics [ 122 ]. However, in practice also diffraction effects can play a role as diffraction pattern can be often seen in the beam reflected from cantilever.…”
Section: Artificial Spm Datamentioning
confidence: 99%